Profil Literasi Budaya Siswa Madrasah Ibtidaiyah Dalam Konteks Cerita Rakyat, Tari Tradisional, Ritual Adat Di Maluku Utara. - Irwan, Risma; Asep, Putri Handayani; Mansur, Indriyani; Lukmana, Dana Arif; Jaohar, Yuliani (Jurnal Ilmiah Wahana Pendidikan, 2023)
Social and cultural literacy is the ability to understand and practice the prevailing values within a society, which distinguish it as unique. Cultural and civic literacy play a crucial role in preserving and developing the local and national cultures present in a society. Cultural literacy is not limited to schools and communities; it also contributes to building the identity of the Indonesian society. Furthermore, cultural and civic literacy are particularly vital in the 21st century and during the Industrial Revolution era in Indonesia, considering the diverse ethnic, linguistic, religious, and social status groups. Maluku Utara is one of the provinces in Indonesia, comprising 8 districts and cities with its capital located in Sofifi. It bears the motto "Marimoi Ngone Futuru," which means "Together We Stand Strong." Initially, the term "Maluku" referred to the four centers of the sultanates in Maluku Utara: Kesultanan Ternate, Kesultanan Tidore, Kesultanan Bacan, and Kesultanan Jailolo. The social and cultural life in Ternate is heavily influenced by Islamic traditions, embraced by Kesultanan Ternate. Moreover, the traditional arts of the region consist of two main types: war and social dances. War dances include cakalele (cakalele, bunga, shosoda, cingari, and sisi) and soya-soya. On the other hand, social dances encompass Anakona/Sigo Yaara, Tide-tide, Togal, Donci, Dinggi Denga, Lala, Sisi, Gala, Kakarongan, Sisi, Gala Haisua, Lalayon, and Dana-Dana, accompanied by traditional musical instruments such as Tifa, Gong, Suling, Filuti Bangseli, Rebana, and Arwas. These traditional arts are distributed throughout the Maluku Utara region. In conclusion, cultural and civic literacy are essential elements in safeguarding and celebrating the rich cultural heritage of Indonesia, particularly in provinces like Maluku Utara, where diverse cultural expressions thrive.